Colombia : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper addresses key areas that would contribute to maintaining macroeconomic stability and inclusive growth. Strong economic growth in Colombia has significantly reduced poverty, but has had limited impact on reducing inequality. Strong growth and social programs have helped reduce poverty. Going forward, efforts to further strengthen education, pension, and tax systems stand to yield important social gains, as recognized by the national development plan. Labor market distortions have declined in recent years, but challenges remain. The elimination of infrastructure gaps will also play a key role in sustaining strong and broad-based growth, and supporting further economic diversification.